Effective utilization of weak alkaline soils with Cd-contamination by wheat and rape intercropping - Xu Li; Yaping Li; Xirui Kang; Jinpeng Yu; Shuo Gao; Jin Zhang; Hui Wang; Hong Pan; Quangang Yang; Yuping Zhuge; Yanhong Lou (Ecotoxicology and Environmental Safety, 2022)
Recently, there has been increasing concern about the health hazards of heavy metal-polluted farmlands. Recent findings suggest that intercropping could be effective remediation strategy for agricultural soils without affecting crop biomass yield. However, there are concerns on the heavy metal accumulation in plant organs in phytoremediation, emphasizing the need to develop an effective intercropping remediation model. In this study, we evaluated the effects of intercropping rape and wheat with different accumulation characteristics of cadmium (Cd), and crop growth and physiological characteristics. Intercropping significantly reduced the Cd content of rape shoot and root, with the rape–low Cd-accumulating wheat intercropping system yielding the best results. However, intercropping had no significant effect on Cd accumulation in wheat. Additionally, intercropping affected the root system configuration and structure, photosynthetic indicators, chlorophyll content, crop enzyme content, and rhizosphere enzyme activity of both species, but did not significantly affect the biomass of wheat and rape. Overall, our findings showed that intercropping rape with a low Cd-accumulating wheat variety could be an effective model for safe production of wheat and rape in weak alkaline soils without compromising biomass yield. The study demonstrates that similar innovative, effective, and judicious intercropping strategy can enrich the theory of contaminated soil remediation.